Dyskursy psychoterapii a rozumienie rzeczywistości społecznej - Józefik, Barbara (Kultura i Społeczeństwo, 2018)
Complex and changing social conditions engender the need to find a language to describe the phenomena and to elucidate their mechanisms. One possibility is the language of psychotherapy, which in itself is complex because it combines the various currents which have emerged in psychotherapy’s more than one hundred years of history. The author’s aim is to analyze the relations between culture, social reality (including Poland’s), and psychotherapy. On the one hand, she attempts to view psychotherapy as a cultural discourse, and on the other, to understand culture and social phenomena from the perspective of a psychotherapy office.